Civics teachers’ assessment practices in Swedish upper secondary schools: A qualitative study. - Jansson, Tobias (JSSE - Journal of Social Science Education, 2023)
Highlights: Civics teachers assess a broad content, but there are some core areas. Different cognitive skills are measured focusing on reasoning skills, characterizing Civics. Teachers use a variety of methods, though written assignments are most common. Contextual factors and teachers’ beliefs strongly affect teacher agency in assessment Purpose: The aim is to qualitatively explore Civics teachers’ assessment decisions regarding content, skills, and methods in Swedish upper secondary schools. Methodology: Thematic analyses of assignments and interviews of thirteen Civics teachers in Swedish upper secondary school. Findings: The open Swedish curriculum and Civics syllabus enables teacher agency in assessment decisions and teachers do not find it necessary to assess all content. The thirteen teachers varied their assessment methods, which are mainly chosen from rationales other than measured content and skills. Teacher agency in assessment decisions is affected by teachers’ experiences and beliefs, Civics canonic traditions, and context, rather than education or curricular demands, except for a performative discourse focusing on grades. Research limitations/implications: Though limited to a small sample in Swedish upper secondary schools and Civics, findings may be applicable in similar open/flexible subjects and similar national contexts.